2020
DOI: 10.1002/lary.29262
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Video Laryngoscopy for Intubation in Severe Pierre Robin Sequence: A Retrospective Review

Abstract: Objectives/Hypothesis The anatomy of children with severe Pierre Robin sequence can present a challenge for direct laryngoscopy and intubation. Advanced techniques including flexible fiberoptic laryngoscopic intubation have been described but require highly specialized skill and equipment. Rigid video laryngoscopy is more accessible but has not been described in this population. Study Design Retrospective cohort study. Methods A retrospective review was completed at a tertiary care center of all children betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…18,19 Visualizing the airway before intubation via direct laryngoscopy with bronchoscopy, drug-induced sleep endoscopy, or other means is important in selecting the appropriate and least invasive treatment. 20 Prone positioning can help with mild respiratory obstruction by moving the tongue forward but is unlikely to be beneficial in severe cases. 21 Early nasopharyngeal tube placement can help open the airway and has minimal morbidity, and thus can be used to avoid tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Visualizing the airway before intubation via direct laryngoscopy with bronchoscopy, drug-induced sleep endoscopy, or other means is important in selecting the appropriate and least invasive treatment. 20 Prone positioning can help with mild respiratory obstruction by moving the tongue forward but is unlikely to be beneficial in severe cases. 21 Early nasopharyngeal tube placement can help open the airway and has minimal morbidity, and thus can be used to avoid tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Visualizing the airway before intubation via direct laryngoscopy with bronchoscopy, drug-induced sleep endoscopy, or other means is important in selecting the appropriate and least invasive treatment. 20…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of complications, direct laryngoscopy is prone to endanger children’s lives due to a high failure rate of intubation[ 13 ]. Although video-laryngoscopy also has high success rates in difficult tracheal intubation[ 9 ], the reported failure rates and severe complications must be taken into account[ 14 ]. To date, there have been fewer hemodynamic responses and adverse events during endotracheal intubation using FB[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Yin et al [ 3 ] reported difficult intubation in 71% of children with PRS before surgery. Therefore, the stomatologists strongly recommended that TI using FB was performed for PRS children preoperatively, which had the following advantages: indication of the location of airway obstruction in children, elimination of airway obstruction below the tongue level, and reduction of the difficulty of endotracheal intubation[ 4 , 9 ]. The previous study indicated that endotracheal intubation using FB is safe and effective even in neonates with PRS[ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Life-saving and function-preserving airway management strategies are available (see Table 1), but routine delivery presents a limited window for intervention. 4,5 Accordingly, preplanning for delivery strategies such as surgical laryngoscopist/airway surgeon attended delivery (AD) and ex utero intrapartum treatment (EXIT) reduces the time from delivery to intervention and prolongs the window for airway intervention, respectively. 5,6 The simultaneous treatment of mother and baby during delivery greatly increases the decision-making complexity.…”
mentioning
confidence: 99%